A receiver aware H.264/AVC encoder for decoder complexity control in mobile applications. Issue 3 (March 2017) - Semsarzadeh, Mehdi; Roodaki, Hoda; Aminlou, Alireza; Hashemi, Mahmoud; Shirmohammadi, Shervin
Abstract Due to the power limitations of mobile devices, high-quality video decoding is still a main concern, because it quickly drains battery. In this paper, an H.264/AVC receiver aware encoder has been designed that (1) takes into account all of the decoder modules of a receiver, unlike existing RAEs that only consider some of these modules and are therefore sub optimal, and (2) is independent of decoder implementations and platforms. Furthermore, a decoder complexity controller has been proposed that reduces the complexity of different decoder modules, while minimum distortion is achieved. Finally, we formulate and solve a generic RAE optimization problem, and apply this solution to control the computational resource allocation at the macroblock level of a RAE. Our experiments indicate that the proposed approach can reduce the complexity of different modules by up to 10 % with no quality degradation. In addition, the average error of the proposed complexity controller is 0.8 %, making the accuracy of the system very close to 1.